HOTS-Based Analysis on English Reading Comprehension Formative Assessment - Agus Husein As Sabiq; Aulia Putri Ardiana (Tarling : Journal of Language Education, 2020)
The Ministry of Education and Culture has directed the assessment model at Higher-order Thinking Skills (HOTS), but in reality, students are less trained in solving the model of this assessment. This cause the learning outcomes of students tend to be less by the teachers. Therefore, the assessments made by teachers should be on the basis of HOTS. This study aimed to find out the assessment level of reading comprehension formative assessment administered by the English teachers in reference to HOTS. This research is classified as quantitative descriptive research involving two English teachers in SMA 2 Brebes. The items of formative assessment are analyzed using the cognitive level of the revised Bloom. As a result, the researchers find that the questions categorized as HOTS level obtain 18 out of 91 questions or (19.78%). Meanwhile, 73 out of 91 questions or (80.22%) are categorized as LOTS level. It can be implied that HOTS based questions are not at the dominant level. However, the test meets the requirements of the minimum standard by the Ministry of Education and Culture in the National Exam (UN) that is between 15%-20%. But, it is still a little bit less to the position of PISA questions which requires 20%.